Multiple endocrine neoplasm type 2b - Report of three cases and review of the literature - Urban, Cícero de Andrade (2022)
Multiple Endocrine Neoplasia lype ílb (MEN-IIh) is an uncommon syndrome inherited in na autossomal dominant pattern, with 100% penetrance and variable expression. This syndrome is marked by the presence of medullary thyroid carcinoma, pheocromociíoma, and diffuse ganglioneuromatosis of the gastrointestinal tract. Patients have a characteristic fades and marfanoid habitas. The autors report three cases of MEN-IIb, two of them are male, with 15,9 years on average. The first clinical expression in all the cases was the growing cervical mass on the site of the thyroid place and marfanoid habitas. The patients underwent total thyroidectomy with bilateral neck dissection for medullary thyroid carcinoma. One patient had pheochromocitoma fouryears after the diagnosis of the thyroid tumor, and underwent surgical treatment. One patient died 2,5 years after diagnosis, and the others are free of ilness one year after diagnosis.